2012
DOI: 10.1016/j.cell.2011.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Transcription Factors Establish Origin Timing and Long-Range Clustering in S. cerevisiae

Abstract: SUMMARY The replication of eukaryotic chromosomes is organized temporally and spatially within the nucleus through epigenetic regulation of replication origin function. The characteristic initiation timing of specific origins is thought to reflect their chromatin environment or sub-nuclear positioning, however the mechanism remains obscure. Here we show that the yeast Forkhead transcription factors, Fkh1 and Fkh2, are global determinants of replication origin timing. Forkhead regulation of origin timing is ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
301
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(328 citation statements)
references
References 75 publications
23
301
2
2
Order By: Relevance
“…2C). It was also recently reported that Forkhead transcription factors, Fkh1 and Fkh2, bind near origins, and their presence can dictate origin timing (Knott et al 2012). We found no correlation between origins with altered timing in Δfkh1fkh2 with nucleosome occupancy (P = 0.194, χ 2 test), suggesting that Fkh1 and Fkh2 affect origin properties independently of nucleosome occupancy (Fig.…”
Section: Nucleosome Occupancy In G1 Correlates With Origin Propertiescontrasting
confidence: 44%
See 3 more Smart Citations
“…2C). It was also recently reported that Forkhead transcription factors, Fkh1 and Fkh2, bind near origins, and their presence can dictate origin timing (Knott et al 2012). We found no correlation between origins with altered timing in Δfkh1fkh2 with nucleosome occupancy (P = 0.194, χ 2 test), suggesting that Fkh1 and Fkh2 affect origin properties independently of nucleosome occupancy (Fig.…”
Section: Nucleosome Occupancy In G1 Correlates With Origin Propertiescontrasting
confidence: 44%
“…For example, Fkh1 and Fkh2 (Knott et al 2012), and the proximity to telomeres and centromeres are known to affect origin properties, but nucleosome occupancy does not significantly correlate with these parameters. Indeed, although orc1-161 abolishes major changes in nucleosome occupancy at origins between G2/M and G1 and greatly disrupts proper origin usage profiles, changes in nucleosome occupancy do not perfectly correlate with the changes in origin activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently the proximal binding of Forkhead transcription factors (Fkh1 and Fkh2) has been implicated in determining early origin activation time (Knott et al 2012). We find that of the 24 origins that replicate early in S. cerevisiae, but later in at least one other sensu stricto species, only seven are reported to be associated with Fkh1 and/or Fkh2 in S. cerevisiae (Supplemental Table S4; Venters et al 2011).…”
Section: Conservation Of Replication Timingmentioning
confidence: 82%